Hacia un modelo de tributación colaborativa en México: La libertad responsable y el cumplimiento de obligaciones tributarias. - Ochoa Torres, José Luis (My University, 2022)
This thesis proposes a paradigm shift in Mexico's fiscal policy towards a collaborative taxation model, arguing that the current adversarial and coercive relationship between tax authorities and taxpayers hinders effective revenue collection and social progress. Drawing on a multidisciplinary framework that integrates law, philosophy, and behavioral economics, the author posits that compliance should be rooted in "responsible freedom" and mutual trust rather than fear of punishment. The work analyzes the foundational principles of subsidiarity, solidarity, and good faith as essential pillars for restructuring the fiscal compact, emphasizing that the state should act as a facilitator in a system where enterprises are recognized as the primary creators of wealth. By examining international best practices, particularly cooperative compliance models from the OECD, the thesis advocates for a system that fosters dialogue, transparency, and reciprocity, thereby reducing conflict, enhancing voluntary compliance, and ensuring a more efficient and just use of public funds for the common good.
Capítulo I. La Empresa -- Capítulo II. Los principios de subsidiariedad, solidaridad y buena fe, y su incidencia en el Derecho Mexicano -- Capítulo III. Autoridad y poder público -- Capítulo IV. Economía y Derecho -- Capítulo V. Autoridad y contribuyentes -- Capítulo VI. La fiscalidad y el gasto público en México -- Capítulo VI. Luces y sombras en la tributación internacional -- Capítulo VII. Luces y sombras en la tributación internacional -- Capítulo VIII. Las Buenas Prácticas en materia tributaria. Una comprobación de la relación cooperativa
Keywords: Derecho - Tesis; Análisis Económico del Derecho; Banco Mundial; Ley de Concursos Mercantiles